Experimental and theoretical evaluation of Cu-Al-Ni shape memory alloys shielding properties at the 511-1333 keV gamma energy range - Salh, Hemn; Saleh, Dedawan S.; Smail, Jahfer M.; Manguri, Hawbir Swara Ahmed; Balo, S. Nevin; Ahmad, Saddon T. (Springer, 2025)
This study used the gamma transmission method to present a systematic experimental analysis of the mass (mu m)and linear attenuation coefficients (mu) of Cu-Al-Ni shape memory alloys. Gamma rays with energies of 0.511 MeV, 0.661 MeV, 1.173 MeV, and 1.333 MeV were, respectively, emitted from point sources 22Na, 137Cs, and 60Co. The results revealed a significant decrease in both the mass attenuation coefficient from 0.08 to 0.05 cm2g-1 and the linear attenuation coefficient from 0.65 to 0.40 cm-1 as the incident gamma energy increased from 0.511 to 1.333 MeV. The obtained experimental results were compared with theoretical data from established databases such as WinXCom and the Photon Shielding and Dosimetry (Phy-X / PSD). Moreover, seven further vital shielding parameters were calculated utilizing the mu m and mu of experimental and theoretical values including total atomic cross-section (sigma a), total electronic cross-section (sigma e), effective atomic number (Zeff), effective electron number (Neff), half (HVL), tenth value (TVL) layer, and mean free path (MFP) for the alloys at different photon energies. Comparative analysis indicated that these Cu-Al-Ni SMAs exhibit promising potential for nuclear applications, closely aligning with the alloys widely discussed in existing.
Keywords: Gamma shielding; Shape memory alloys; Cu-Al-Ni; Gamma attenuation coefficients; NaI(Tl) detector